Sartrean Existentialism and Ethical Decision-Making in Business - West, Andrew (Journal of business ethics, 2007)
A wide range of decision-making models have been offered to assist in making ethical decisions in the workplace. Those that are based on normative moral frameworks typically include elements of traditional moral philosophy such as consequentialist and/or deontological␣ethics. This paper suggests an alternative model drawing on Jean-Paul Sartre’s existentialism. Accordingly, the model focuses on making decisions in full awareness of one’s freedom and responsibility. The steps of the model are intended to encourage reflection of one’s projects and one’s situation and the possibility of refusing the expectations of others. A case study involving affirmative action in South Africa is used to demonstrate the workings of the model and a number of strengths and weaknesses are identified. Despite several weaknesses that can be raised regarding existential ethics, the model’s success lies in the way that it reframes ethical dilemmas in terms of individual freedom and responsibility, and in its acceptance and analysis of subjective experiences and personal situations.